TRAINING TO STRENGTHEN FAMILY INDEPENDENCE TO PREVENT STUNTING - Ahmad Riadi (Wealth Community Empowerment, 2025)
Indonesia is a country with a prevalence of stunting fifth largest and can hamper economic growth,increasing poverty and widening inequality. The aim of this community service is to increase competence and strengthen family independence in preventing stunting. The method of implementing this service is carried out by counseling, which is divided into several stages activities to optimize Cadre's independent abilities,Pregnant women, Breastfeeding mothers and Teenagers. The results of the activity went well, accompanied by discussions and questions and answers about the pocket books provided as an alternative in increasing the knowledge of health cadres, breastfeeding mothers, pregnant mothers and teenagers.